A call to action to include disability in intersectional health equity research and policy - Susan M. Havercamp; Gloria L. Krahn; Alexa J. Murray; Ilhom Akobirshoev; Chyrell D. Bellamy; Alexandra Bonardi; Mary Lou Breslin; Ly Xīnzhèn Zhǎngsūn Brown; Mark Costa; Robert S. Dembo; David Ellsworth; Jean P. Hall; et al. (The Lancet Regional Health. Americas)
Summary: Disability status is rarely included in health research and policy, including intersectional research, perpetuating health inequities for this population. This paper calls on researchers and policymakers to take concrete steps to advance health equity for disabled people, including those at the intersections of disability, race, ethnicity, poverty, and other marginalized identities. We propose four strategies with recommendations to promote: a) meaningful engagement of disabled and multiply marginalized people in research and policy planning; b) cohesive, systemic disability data collection and analyses; c) use of intersectional approaches to examine structural drivers of health inequities; and d) leveraging of administrative data to improve disability healthcare policies and practices.